A COMPARATIVE STUDY OF INTRATHECAL BUPIVACAINE WITH BUPIVACAINETRAMADOL AND BUPIVACAINE-FENTANYL FOR POST-OPERATIVE PAIN RELIEF IN LOWER ABDOMINAL AND LOWER LIMB SURGERIES - DR ALOK PRATAP SINGH (International Journal of Pharma and Bio Sciences, 2015)
This clinical study was undertaken to evaluate and compare the efficacy of intrathecal bupivacaine, intrathecal bupivacaine with tramadol and bupivacaine with fentanyl for post-operative pain relief in lower abdominal and lower limb surgeries. 90 patients were given either of the three sets of intrathecal drugs randomly so the each group comprised 30 patients. Group A – bupivacaine HCL 15 mg (3ml) 0.5% heavy Group B – bupivacaine HCL 15 mg (3ml) 0.5% heavy and tramadol HCL 25 mg (0.5ml) Group C – bupivacaine HCL 15 mg (3ml) 0.5% heavy and Fentanyl citrate 25 µg (0.5ml) The mean time of onset of sensory block seen in different groups was found to be 110.10+10.02 sec. in Group A, 110.8+11.17 sec in Group B and 112.87+9.65 sec in Group C. The mean duration of sensory block was 3.38+0.21, 4.58+0.46 and 6.86+0.75 hrs in Group A, B and C respectively In the present study mean time of onset of motor block was 254+49.22, 250+44.45, 267.3+42.88 sec in Group A, B and C respectively The mean pulse rate/min before intrathecal injection was 84.80+11.10, 85.56+13.05, 86.13+14.47 in Group A, Group B and Group respectively. The differences were statistically insignificant The mean respiratory rate/min before intrathecal injection in this study was 16.23+1.4, 15.91+3.02, 16.38+2.34 in Group A, Group B and Group C respectively.